2020
DOI: 10.3390/polym12071436
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and In-Vivo Study of Micro-Colloidal Zanthoxylum acanthopodium-Loaded Bacterial Cellulose as a Burn Wound Dressing

Abstract: Bacterial cellulose (BC) is a biopolymer commonly used for wound dressing due to its high biocompatible properties either in-vitro or in-vivo. The three-dimensional fiber structure of BC becomes an advantage because it provides a template for the impregnation of materials in order to improve BC’s properties as a wound dressing, since BC has not displayed any bioactivity properties. In this study, micro-colloidal Zanthoxylum acanthopodium (MZA) fruit was loaded into BC fibers via an in-situ method. Z. acanthopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…However, when the other amorphous biopolymers (chitosan and/or collagen) were added to BC, these peaks become broadened and the intensity of peaks decreased. As a result, the crystallinity index (CrI) of prepared wound dressing was reduced [7,36]. Moreover, it can be seen from Table 1 that the CrI number of pure BC at 92.88% was noticeably higher compared to BC/Chi/Col and BC/Col/Chi wound dressing CrI, where it were calculated to be 73.80 and 73.01%.…”
Section: Analysis Of Xrdmentioning
confidence: 95%
See 1 more Smart Citation
“…However, when the other amorphous biopolymers (chitosan and/or collagen) were added to BC, these peaks become broadened and the intensity of peaks decreased. As a result, the crystallinity index (CrI) of prepared wound dressing was reduced [7,36]. Moreover, it can be seen from Table 1 that the CrI number of pure BC at 92.88% was noticeably higher compared to BC/Chi/Col and BC/Col/Chi wound dressing CrI, where it were calculated to be 73.80 and 73.01%.…”
Section: Analysis Of Xrdmentioning
confidence: 95%
“…Unfortunately, these dressings do not actively enhance the healing process. Recently, several studies carried out in the area of wound management, indicated that a good dressing must play an active role in the healing process [5][6][7][8]. Other research reported that an active wound dressing is not only required to be able to cover the wound in order to avoid contamination and infection but it must also be able to provide sufficient air circulation and removal of wound exudate.…”
Section: Introductionmentioning
confidence: 99%
“…Consumption of “dadih”, a traditional fermented buffalo milk, is common among Indonesian Malays. In addition, Indonesian Malays commonly consume Zanthoxylum acanthopodium , spicy flavored fruits [ 25 ]. Both Zanthoxylum acanthopodium and “dadih” have anti-microbial activity against several gram-positive and gram-negative pathogenic bacteria [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, a good wound dressing must meet a number of conditions, such as preventing the growth of pathogenic bacteria and absorbing the exudate of the wound while still maintaining the moisture content of the wound, supporting the process of tissue regeneration and accelerating the process of wound healing [9][10][11]. Nanomaterials, such as AgNPs, have recently sparked interest because the synthesis process is capable of being carried out and conditioned in a variety of ways, depending on the needs and subsequent use [5,8,12,13].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%